Microwave-Modified Reactor to Enhance the Properties and Efficacy of ZnO/GO Nanocomposites in High-Performance Methylene Blue Photocatalysis - Agusu, La; Darusman, La Ode Muhammad; Alimin, Alimin; Kadidae, La Ode; Zaeni, Ahmad; Ahmad, La Ode; Muhamad, Fadel; Sutapa, I Wayan; Ishikawa, Yuya; Nakagawa, Kohei; Fujii, Yutaka; Asano, Takayuki; et al. (Trends in Sciences, 2025)
This study investigates the synthesis and photocatalytic performance of ZnO/Graphene Oxide (GO) nanocomposites utilizing a modified microwave reactor heating technique. The ZnO/GO nanocomposites were successfully fabricated through a hydrothermal process followed by microwave irradiation. The incorporation of GO into ZnO nanoparticles significantly enhanced photocatalytic efficiency by mitigating electron-hole recombination, a notable limitation associated with pure ZnO. The application of microwave heating improved the crystallinity and uniformity of ZnO, resulting in larger particle sizes compared to those produced through conventional heating methods. This observation is observation by microstructural analysis, which indicates that the dislocation density, microstrain, and stress values in ZnO nanoparticles synthesized via conventional methods are higher than those produced by the microwave method. Furthermore, the energy density associated with conventional synthesis is lower than that achieved with the modified microwave reactor approach. Microwave heating facilitates a reduction in the band gap of the ZnO/GO composite to 2.22 eV, in contrast to the 2.62 eV observed in conventionally heated ZnO. This reduction in band gap energy enhances light absorption, thereby augmenting photocatalytic activity. Photocatalytic experiments demonstrated that ZnO/GO nanocomposites effectively degraded 87.4% of methylene blue (MB) dye under UV light and 66.6% under visible light within 50 minutes of irradiation. HIGHLIGHTS Highlights We prepared ZnO/graphene oxide (GO) nanocomposites through a hydrothermal process followed by modified microwave reactor heating. Modified microwave reactor heating with the presence of GO improved the crystallinity and prevented rapid grain growth Modified microwave reactor heating reduces the band gap of ZnO/GO nanocomposites, enhancing visible light absorption The ZnO/GO nanocomposites achieve a high degree of methylene blue (MB) degradation under UV and visible light irradiation. Modified microwave reactor synthesis coupled with GO integration provides a promising strategy for developing high-performance photocatalysts for environmental remediation. GRAPHICAL ABSTRACT